Diseño de un proceso administrativo de la Dirección Administrativa de Desarrollo Institucional del IMDER Palmira, a través de la implementación del Modelo Integrado de Planeación y Gestión-MIPG (2020)
The Municipal Institute of Sport and Recreation, IMDER Palmira, as an organization of the Colombian State, must identify opportunities for improvement to meet the needs and problems of physical health and guarantee the rights of all to participate in its events. To achieve this purpose, the Integrated Planning and Management Model (2020), MIPG, is available as a tool that simplifies and integrates administrative development and quality management systems to make them simple and efficient. The objective of this study was to design a quality management procedure that would allow the effectiveness and efficiency of the process of the administrative management of development of IMDER Palmira. For this purpose, the research question addressed was: What is the design that allows the effective and efficient development of the administrative process of the administrative directorate of institutional development of IMDER Palmira, Valle del Cauca, in the implementation of the Integrated Model of Planning and Management-MIPG? A quantitative approach to research, descriptive, taking as a case study the IMDER Palmira, used the techniques of interviewing and applying the Single Format Tool for Reporting and Advancement of Management, FURAG II. The results yielded allowed the design of the steps and procedures of each of the value routes of the IMDER Palmira administrative management process. It is concluded that, through the application of the Single Format of Reporting and Advancement of Management, FURAG II, the design of steps and procedures for each of the micro routes that were generated in the self-assessment of the quality system of the IMDER Palmira, which will serve as implementation in the administrative direction institutional development and contribute to the effectiveness and effectiveness of its functions.. Each of the procedures designed have process name, thread, procedure name, objective, scope, procedure steps, responsible, required support documents and formats to demonstrate compliance registration, giving the rigor of ISO 9001:2015. This proposal of processes and procedures for the administrative direction institutional development of the IMDER Palmira, shows how to contribute to the Integrated Quality System, SIC, from an interpretation of FURAG II, to ensure the efficiency and effectiveness of the operational performance of an organizational unit and the detection of threats that may affect in the future the activities planned by the organization. Keywords: Effective, Efficient, Procedure, Value Path, Integrated Quality System.